A modeling approach to compute modification of net joint forces caused by coping movements in obstetric brachial plexus palsy - Kleiber, Tim; Popovic, Nikica; Bahm, Jörg; Disselhorst-Klug, Catherine (Journal of Brachial Plexus and Peripheral Nerve Injury, 2013)
Background Many disorders of the musculoskeletal system are caused by modified net joint forces resulting from individual coping movement strategies of patients suffering from neuromuscular diseases. Purpose of this work is to introduce a personalized biomechanical model which allows the calculation of individual net joint forces via inverse dynamics based on anthropometry and kinematics of the upper extremity measured by 3D optoelectronical motion analysis.Methods The determined resulting net joint forces in the anatomical axis of movement may be used to explain the reason for possible malfunction of the musculoskeletal system, especially joint malformation. For example the resulting net joint forces in the humerothoracic joint from simulations are compared to a sample of children presenting obstetric brachial plexus palsy showing an internal shoulder rotation position and a sample of healthy children.Results The results presented from the simulation show that an increased internal shoulder rotation position leads to increased net joint forces in the humerothoracic joint. A similar behavior is presented for the subjects suffering from brachial plexus palsy with an internal shoulder rotation position.Conclusions The increased net joint forces are a possible reason for joint malformation in the humerothoracic joint caused by coping movements resulting from neuromuscular dysfunction as stated in literature.
Keywords: Biomechanics; Kinematics; Kinetics; Internal shoulder rotation; Inverse dynamic; Joint malformation